NUTRITIONAL VALUE AND ANTIOXIDANTS CAPACITY OF FOUR FRUITS OF NATIVE PALM TREES FROM THE PERUVIAN AMAZON - VARGAS-ARANA, Gabriel (2022)
Currently there is a trend towards the consumption of foods that provide health benefits, as is the case of palm fruits that are of great importance as a food source and for their medicinal use. In the present study the nutritional value and antioxidant activity of ungurahui (Oenocarpus bataua), sinamillo (Oenocarpus mapora), asaí (Euterpe oleracea) and huasaí (Euterpe precatoria), palm fruits native to the Peruvian Amazon were evaluated. The proximal composition and physicochemical properties were analyzed by official methods, the micro and macro nutrients by atomic absorption spectroscopy and the composition of fatty acids by gas chromatography. The evaluation of the antioxidant activity was carried out using the DPPH and ABTS methods. The four fruits have a good content of proteins and carbohydrates, as well as a high content of K, Cu and Mn. The oils extracted from the fruits have a high content of saturated fatty acids (70.78-83.27%), with oleic acid being the majority in all cases. All the fruits presented antioxidant activity values ​​higher than those reported for other exotic fruits, with sinamillo being the fruit that presented the best activity in both tests (DPPH 116.58 µmol TE/g FS, ABTS 239.22 µmol TE/g FS). These results indicate that the fruits of palm trees from the Peruvian Amazon have a high nutritional value and that they can be used for the production of functional foods or food supplements.